Development of Groundnut Digger Blade Suitable for a Small Tractor - Tiwari, V K; Jethva, K R (Journal of Agricultural Engineering, 2001)
Efforts were made to develop a two-row groundnut digger blade driven by a small tractor. The blade was tested and compared with other existing traditional blades. The effective field capacity, field efficiency, harvesting efficiency and fuel consumption for the blade are 0.126 ha/h, 77.8 %, 94% and 2.4 lit/ha, respectively.